IMPLEMENTASI WAKAF PRODUKTIF BERBASIS QA’IDAH DAR’ AL-MAFASID MUQADDAM ALA JALB AL-MASALIH: ANALISIS DIMENSI SYARIAH TERHADAP RISIKO PENGELOLAAN WAKAF - Imam Kamaluddin; Syamsuar, Mushaq (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2026)
The transformation of waqf into productive sectors introduces complex risk exposures that may lead to the loss of the principal asset (ḍayāʿ al-aṣl), directly contradicting the perpetual principle of taḥbīs al-aṣl. Existing literature is largely dominated by a benefit-maximization approach (jalb al-maṣāliḥ), thereby leaving a research gap in the form of a limited normative fiqh framework for risk prevention. To address this gap, this study aims to reconstruct risk management by positioning the legal maxim Dar’ al-Mafāsid Muqaddam ʿalā Jalb al-Maṣāliḥ as a foundation for substantive mitigation. Employing a normative legal research method with a juridical-normative approach, secondary data are analyzed through hermeneutic interpretation and synthesis. The findings reveal that the principle of preventing harm (dar’ al-mafāsid) necessitates prioritizing loss prevention over the pursuit of speculative benefits. Consequently, the application of this maxim demands a high standard of Sharīʿah prudentiality and significantly transforms the role of the nāẓir from a mere investment manager into a trustee. Overall, this study contributes theoretically by operationalizing a fiqh-based legal maxim to ensure prudence in the governance of productive waqf